Pengembangan E-modul Informatika Berbantuan Heyzine Flipbook Pada Elemen Literasi Digital - Hidayah, Anissatul; Saputra, Galih Yudha (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This development research is motivated by the unavailability of an informatics guidebook that discusses digital literacy elements according to the learning outcomes of the independent curriculum based on a Decree from the Curriculum Standards and Education Assessment Agency Number 032/H/KR/2024. Therefore, as a solution, the development of an informatics e-module on digital literacy elements is carried out with the aim of assessing the feasibility level of the product. This research is classified as a development category with the application of 4D models, which consists of 4 stages, namely Define, Design, Development, and Disseminate. The feasibility data of the e-module was obtained from filling out a questionnaire through 1 material expert validator, 3 media expert validators, and a limited trial of the e-module product involving 35 students. The results of the recapitulation of the average score of the feasibility test through 1 material expert showed that the number 68 covered the > range of 63 including the category of